Sosialisasi Tentang Ulasan Undang-Undang No. 17 Tahun 2023 Tentang Kesehatan - Satria Indra Kesuma (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study uses a sociological juridical approach to analyze the relationship between legal protection and a supportive work environment on doctors' ability to provide optimal health services. The results of this study outline various factors such as workload, availability of medical facilities and equipment, and policies that value work-life balance, into important aspects discussed. Through this approach, research not only analyzes relevant legal aspects, but also explores the social factors that influence the practice of medicine in hospitals. In overcoming the challenges of high workloads and maintaining quality of services, it is important for hospitals and relevant stakeholders to create a supportive environment, including providing adequate facilities and implementing policies that take into account doctors' work-life and personal life balance. The findings of this study are expected to provide richer insights into the issue of legal protection and comfort in medical practice in hospitals and their impact on the quality of health services provided by doctors.